The Pursuit of Sustainable Competitive Advantages: A Study of Dynamic Capabilities within the Company Balfour Beatty - Chang, Hui-Chun (2012)
Facing a rapidly changing environment, possessing sustainable competitive advantage seems more difficult to a firm. Dynamic capabilities, an alternative strategic framework to gain competitive advantage, highlight the potential value of modifying a firm’s resource base in order to become more adaptive to the dynamic environment. Continuing the managing project that aims to identify foreign market entry strategy in Asian markets for Balfour Beatty Rail, this paper attempts to provide an insight into how dynamic capabilities can underpin Balfour Beatty’s competitiveness with the respect to strategic alliances and acquisitions. After the analysis based on the case of Balfour Beatty, two specific areas, process and position, will be further discussed and the important managerial implications will be provided.